Pengaruh Current Ratio, Sales Growth, Net Profit Margin dan Firm Size. Terhadap Harga Saham: pada Perusahaan Pertambangan yang terdaftar di Bursa Efek Indonesia (BEI) periode 2016-2022 - Nurul Aisyah, Siti; Kusumawardhani, Astrin (Masyarakat Ekonomi Syariah Bogor, 2024)
The purpose of this research is to ascertain how Return on Assets in Mining Companies Listed on the Indonesia Stock Exchange is affected by Current Ratio, Sales Growth, Net Profit Margin, and Firm Size between 2015 and 2022. This study employs a quantitative methodology that combines a verification and descriptive strategy. Various statistical tests are employed in hypothesis testing, including partial and simultaneous tests (t and f tests), multiple linear regression tests, Pearson product moment correlation coefficient tests, determination coefficient tests, and classical assumption tests. 56 mining companies' financial reports provided the sample data. Purposive sampling combined with nonprobability sampling is being used. IBM SPSS version 26.0 was the analysis tool used in this investigation. Current Ratio has a considerable impact on stock price, according to study data. A major factor influencing stock price is sales growth. The stock price is not influenced in part by firm size or net profit margin. According to the study's findings, the stock price is significantly impacted by the concurrently obtained current ratio, sales growth, net profit margin, and company size.